Essentials in the Treatment of COVID-19 - Rad, Fatemeh M.; Elyasi, Hossein; Rahimi, Hadis; Zamani, Amir; Nafari, Amirhossein (Anti-Infective Agents, 2021)
Background: There are many coronaviruses, which can cause diseases in humans and animals. The new 2019 coronavirus is highly prevalent and contagious, infecting many people in almost all countries of the world. There are many problems involved in the treatment of COVID-19 that must be discussed and examined. Methods: A double-blinded review was conducted on double-blinded studies found on online databases, such as Google Scholar, PubMed, Science Direct, Medline, Highwire, MD Consult, and Scopus, by Internet-based search. Results: Many deaths attributing to COVID-19 are actually caused by mistakes made in the prescription of medications, leading to the deterioration of the conditions of the patients, the most serious of which is the prescription of corticoids. Additionally, it has not been properly researched whether some drugs, such as NSAIDs, are indicated for use in COVID-19 or not. Conclusion: On the other hand, the application of some valuable medicinal herbs, such as peppermint and chamomile, in the treatment of this disease has not received enough attention, despite the fact that they may have valuable and remarkable effects in the treatment of this disease.
Keywords: virus